Public Discourses of Ebola Contagion and Courtesy Stigma: The Real Risk to International Health Care Workers Returning Home From the West Africa Ebola Outbreak?. (July 2018) - Gee, Stephanie; Skovdal, Morten
This article explores the homecoming experiences of international health care workers who responded to the 2014 to 2016 West African Ebola outbreak. Interviews with 11 frontline international medical staff were undertaken and data thematically analyzed. It was found that international health care workers faced an unforeseen risk of stigmatization upon their return home, related to others' fears of their infectious status. Media representations of the disease appear to have played a significant role in heightening societal perceptions of the risks associated with the returning health care workers, resulting in public hostility toward them. For participants, these social risks overtook concerns about biological risks during the immediate postmission period. The participants developed different strategies to cope with courtesy stigma, by rationalizing stigmatizing attitudes, educating people, or simply through an avoidance of others.